A Perspective on Accelerated Aging Caused by the Genetic Deficiency of the Metabolic Protein, OPA1 - Erchova, Irina; Sun, Shanshan; Votruba, Marcela (Frontiers in Neurology, 2021)
Autosomal Dominant Optic Atrophy (ADOA) is an ophthalmological condition associated primarily with mutations in the OPA1 gene. It has variable onset, sometimes juvenile, but in other patients, the disease does not manifest until adult middle age despite the presence of a pathological mutation. Thus, individuals carrying mutations are considered healthy before the onset of clinical symptoms. Our research, nonetheless, indicates that on the cellular level pathology is evident from birth and mutant cells are different from controls. We argue that the adaptation and early recruitment of cytoprotective responses allows normal development and functioning but leads to an exhaustion of cellular reserves, leading to premature cellular aging, especially in neurons and skeletal muscle cells. The appearance of clinical symptoms, thus, indicates the overwhelming of natural cellular defenses and break-down of native protective mechanisms.